Carbon Taxation and Its Role in Promoting Renewable Energy Adoption - Sreekar Rayaprolu, Pranav (Digital Repository of Theses, 2025)
The influence of carbon taxation in supporting renewable energy and sustainability is the focus of this research. The primary aim is thus to measure attitudes towards carbon taxation, regarding the efficiency of the instrument and its impact on behavior as well as on the advancement of renewable energies. Additionally, the study explores relationships between attitudes toward carbon taxation, perceived effectiveness, and adoption behaviors. The research utilizes a quantitative methodology, employing a structured survey to collect data from a diverse sample of respondents. The survey is designed to measure key constructs such as attitude towards carbon taxation, subjective norms regarding carbon taxation, perceived behavioral control over renewable energy adoption, behavioral intention to adopt renewable energy and perceived effectiveness of carbon taxation in achieving environmental goals. A survey of 100 participants assessed attitudes, behavioral intentions, and actual adoption patterns related to renewable energy. Statistical analyses, including Spearman’s correlation and logistic regression, evaluated the relationships between key variables such as attitudes toward carbon, and renewable energy adoption. As for the findings, they demonstrate rather positive attitudes towards carbon taxation as a tool to punish offenders and motivate green innovators as well as encourage sound practices. The level of perceived effectiveness of carbon taxation affects both behavioral intention and adoption behavior; behavioral intention was instrumental in increasing high levels of renewable energy adoption. Therefore, the study finds that carbon taxation is a suitable policy tool for decarbonizing energy and managing climate change. However, this success depends on fair implementation and other synergy activities like subsidizing “Renewable Energy Sources” (RES) and raising awareness. The implications of this research are important for policymakers, suggesting that carbon taxation has both economic and behavioral consequences to which appropriate attention should be paid when designing and implementing carbon taxation systems. It entails nurturing support from the public, how the taxes have been structured and better policies on RES. The findings contribute to growing body of literature advocating for carbon taxation as a critical tool in achieving environmental sustainability and transitioning toward a low-carbon economy.